Indeks Formula Eritrosit Untuk Uji Skrining Talasemia Beta Minor - Setiawan, Doni; Setiawan, Hendri; Nurmalasari, Ary (Jurnal Analis Medika Biosains (JAMBS), 2021)
Erythrocyte indices have been used as the first indicator in screening for beta-thalassemia minor. However, iron deficiency in hemoglobinopathies can reduce the sensitivity of screening, and the spectrum of mutations of different hemoglobinopathies between populations will result in discontinuation of the results of different erythrocyte indices. The research objective in this study was to determine the description of the erythrocyte indices used to screen for beta-thalassemia trait in Ciamis. The research method used in this study was a quantitative descriptive, using a cross-sectional study, data collection had been done during March-May 2021. The subjects of this study were 104 parents of a beta-thalassemia trait who have children with a beta-thalassemia major in Ciamis. The examination parameters used were complete blood count, with processing twenty-six erythrocyte formula index values. Ninety-two respondents were included in the inclusion criteria. The results of the erythrocyte indices in beta-thalassemia trait are England and Fraser, RBC, Mentzer, Srivastava, Shine and Lal, Ricerca, Green and King, Das Gupta, Jayabose, Telmissani-MCHD, Telmissani-MDH, Huber-Herklotz, Kerman I, Kerman II, Sirdah, Ehsani, Keikhaei, Nishad, Wongprachum, Sehgal, Pornprasert, Sirachainan, Bordbar, Matos and Carvalho and CRUISE has cut-off value in that range according to previous studies. Only the Bessman erythrocyte indices has a value of 17, exceeding the cut-off. Twenty-five erythrocyte indices with cut-off value according to previous studies can be used for beta-thalassemia screening in Ciamis, except for the Bessman erythrocyte indices.